2020
DOI: 10.1371/journal.pntd.0008146
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective epidemiological analysis of human Cryptosporidium infection in China during the past three decades (1987-2018)

Abstract: Background Cryptosporidiosis is an emerging infectious disease of public health significance worldwide. The burden of disease caused by Cryptosporidium varies between and within countries/ areas. To have a comprehensive understanding of epidemiological status and characteristics of human Cryptosporidium infection in China since the first report in 1987, a retrospective epidemiological analysis was conducted by presenting differences in the prevalence of Cryptosporidium by province, year, population, living env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 95 publications
3
60
2
Order By: Relevance
“…C. parvum and C. hominis are recognized as the main causative agents (> 90%) in reported human cases of Cryptosporidium infection (Squire and Ryan, 2017;Liu et al, 2020). However, in the present study, two unusual Cryptosporidium species were identified: C. andersoni (n = 2) and C. viatorum (n = 1).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…C. parvum and C. hominis are recognized as the main causative agents (> 90%) in reported human cases of Cryptosporidium infection (Squire and Ryan, 2017;Liu et al, 2020). However, in the present study, two unusual Cryptosporidium species were identified: C. andersoni (n = 2) and C. viatorum (n = 1).…”
Section: Discussioncontrasting
confidence: 61%
“…Children are reported to have a statistically significantly higher prevalence than adults: such as 2.56% versus 1.89% for Cryptosporidium spp. in China (Liu et al, 2020); 53.2% versus 22.2% for G. duodenalis in Uganda (Johnston et al, 2010). Meanwhile, some studies reported significant difference in prevalence of both parasites between diarrheal and non-diarrheal children, such as 16.3% versus 3.1% for Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, Cryptosporidium spp. and G. duodenalis have been found in more than 27 provincial administrative regions in China ( Yang et al, 2017 ; Liu et al, 2020 ). However, there continues to be a critical lack of surveillance systems documenting and tracking protozoan infection and waterborne outbreaks in developing countries ( Baldursson & Karanis, 2011 ; Efstratiou, Ongerth & Karanis, 2017a ; Efstratiou, Ongerth & Karanis, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, Cryptosporidium spp. and G. duodenalis have been found in more than 27 provincial administrative regions in China (Yang et al, 2017;Liu et al, 2020). However, there continues to be a critical lack of surveillance systems documenting and tracking protozoan infection and waterborne outbreaks in developing countries (Baldursson & Karanis, 2011;Efstratiou, Ongerth, & Karanis, 2017ab).…”
Section: Introductionmentioning
confidence: 99%